Differential diagnosis in neuroimaging. - Meyers, Steven P. (Thieme, 2017)
Authored by renowned neuroradiologist Steven P. Meyers, Differential Diagnosis in Neuroimaging: Brain and Meninges is a stellar guide for identifying and diagnosing brain pathologies based on location and neuroimaging results. The succinct text reflects more than 25 years of hands-on experience gleaned from advanced training and educating residents and fellows in radiology, neurosurgery, and neurology. The high-quality MRI, CT, PET, PET/CT, conventional angiography, and X-ray images have been collected over Dr. Meyers's lengthy career, presenting an unsurpassed visual learning tool. The distin